The health risk assessment of heavy metals to human health through the consumption of Tilapia spp and catfish caught from Lake Mariut, Egypt. Issue 7 (July 2022) - Hasanein, Soha S.; Mourad, Mohamed H.; Haredi, Afaf Mohamed M.
Abstract: This work assesses the concentration of As, Cd, Pb, Hg, and Al in three of Tilapia species and catfish caught from Lake Mariut. As well as the human health risk and muscle biochemical composition. Besides, the antioxidant responses of different species. The average metal concentration order was Pb> As> Cd> Al> Hg. The Cd and Pb levels in all species; besides, the Hg levels in Oreochromis niloticus and Oreochromis aureus exceeded the maximum limits set by FAO, European legislation, and FAO/WHO. The human health risk was assessed using estimated dietary intakes, the target hazard quotient (THQ), and the carcinogenic risk (CR). THQAs was >1 in all examined fishes and closer to 1 in THQCd, Hg . As well, CR level for As was higher than the permissible value. Tilapia zillii showed significant decreases in carbohydrates compared to Clarias gariepinus ; also, ash content compared to C. gariepinus, O. niloticus, and O. aureus . Furthermore, water content compared to O. aureus . In contrast, significant increases of SOD in O. niloticus compared to C. gariepinus . In addition, CAT and GPx in O. aureus compared to C. gariepinus . Also, GR in both O. niloticus and O. aureus compared to C. gariepinus, and GSH in all of Tilapia spp. compared to C. gariepinus . Data obtained provide evidence of health risks to the consumers. Therefore, more caution is required. Highlights: The levels of As, Cd, Pb, Hg and Al were measured in the flesh of C. gariepinus, O. niloticus, O. aureus, and T. zillii fish. Association between the potential risk of HMs exposure and the consumption of fish by adults, youth, and children was studied. Estimated dietary intakes, target hazard quotient, and the carcinogenic risk were used to assess the human health risk.